Reviews and Responses for Modelling ADS-B Reception Probability Using OpenSky Data - Rahman, Muhammad Fazlur; Ellerbroek, Joost; Hoekstra, Jacco; Lenders, Vincent; Schäfer, Matthias (Journal of Open Aviation Science, 2025)
See detailed reviews and responses in the PDF file. DOI for the original paper: https://doi.org/10.59490/joas.2024.7895